2008
DOI: 10.1177/0886260507309340
|View full text |Cite
|
Sign up to set email alerts
|

Violence in Young Adolescents' Relationships

Abstract: A structural equation model based on social cognitive theory was used to predict relationship violence from young adolescents' knowledge, self-efficacy, attitudes, and alternative conflict strategies (n = 143 male and 147 female grade 7-9 students). A direct causal effect was supported for violence-tolerant attitudes and psychologically aggressive (escalation/blame) strategies on physical violence against dating partners and friends. Knowledge and self-efficacy contributed to using reasoning-based strategies, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
37
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 28 publications
3
37
0
Order By: Relevance
“…Therefore, even though these behaviors may not be viewed as violent when asked directly, this discrepancy finding supports the need for education that involves the definition of violent and unhealthy behaviors in romantic relationships. Indeed, the behaviors categorized as psychological aggression have been linked to negative outcomes (e.g., Holt & Espelage, 2005;Zayas & Shoda, 2007) and are often precursors to physical violence (e.g., Calvete, Corral, & Estevez, 2008;Josephson & Proulx, 2008). Therefore, the aforementioned behaviors that constitute psychological aggression should be addressed in relationship education programs along with physically violent behaviors.…”
Section: Discussionmentioning
confidence: 96%
“…Therefore, even though these behaviors may not be viewed as violent when asked directly, this discrepancy finding supports the need for education that involves the definition of violent and unhealthy behaviors in romantic relationships. Indeed, the behaviors categorized as psychological aggression have been linked to negative outcomes (e.g., Holt & Espelage, 2005;Zayas & Shoda, 2007) and are often precursors to physical violence (e.g., Calvete, Corral, & Estevez, 2008;Josephson & Proulx, 2008). Therefore, the aforementioned behaviors that constitute psychological aggression should be addressed in relationship education programs along with physically violent behaviors.…”
Section: Discussionmentioning
confidence: 96%
“…Initial findings reveal that traditional sex-role beliefs, increased feelings of romantic jealousy, and higher levels of interpersonal and verbal aggression in the past were found to predict expressed violence among females (Bookwala et al, 1992). Positive attitudes toward male and female perpetrated dating violence have also been linked with greater acceptance of the use of violence outside of dating relationships (Josephson & Prouix, 2008). Due to this connection between accepting attitudes toward dating violence and the actual perpetration of violence, dating violence prevention programs have been developed for college students that target dating violence attitudes as a way to reduce actual perpetration (Schwartz, Griffin, Russell, & Frontaura-Duck, 2006).…”
Section: Attitudes Toward Dating Violencementioning
confidence: 99%
“…This area of research has been more developed in terms of dating violence prevention, where attitudes supporting dating violence have been shown to influence involvement in dating violence. [29][30][31] Few studies have addressed attitudes supporting violence and their associations with peer violence. One study found that among youth in grades 7 through 9, aggressive attitudes were significantly associated with peer violence perpetration among youth.…”
Section: Introductionmentioning
confidence: 99%